Modern Java in action : lambda, streams, functional and reactive programming - Urma, Raoul-Gabriel (Manning Publications, 2019)
Modern applications take advantage of innovative designs, including microservices, reactive architectures, and streaming data. Modern Java features like lambdas, streams, and the long-awaited Java Module System make implementing these designs significantly easier. It's time to upgrade your skills and meet these challenges head on!